Motivasi Belajar Matematika Siswa: Sebuah Tinjauan Teoritis - Saman (Polinomial : Jurnal Pendidikan Matematika, 2025)
Learning motivation is a crucial factor influencing students’ success in understanding and mastering academic subjects, including mathematics. This article aims to examine various motivation theories and their implications for mathematics learning at the school level. Using a Systematic Literature Review (SLR) approach, this study explores major theories such as the Self-Determination Theory, Expectancy-Value Theory, Attribution Theory, and the concept of self-efficacy. The review process follows the guidelines of Snyder (2019) and Boell & Cecez-Kecmanovic (2015) through four stages: topic identification, literature search, article selection based on inclusion–exclusion criteria, and data analysis and synthesis. Literature sources were obtained from Google Scholar, Scopus, DOAJ, and SINTA databases, covering publications from 2010 to 2024. The findings indicate that the proper application of motivational theories can enhance students’ engagement, confidence, and persistence in learning mathematics while strengthening the teacher’s role as an effective learning facilitator.